Accessibility in HCI: Analyzing Inclusive Design Principles and Techniques for Ensuring Accessibility to Interactive Systems for Users With Disabilities (Human-Computer Interaction Perspectives, 2024)
Accessibility in Human-Computer Interaction (HCI) is crucial for ensuring that interactive systems are usable by individuals with disabilities. Inclusive design principles and techniques play a pivotal role in creating accessible interfaces that cater to diverse user needs. This paper examines the significance of inclusive design in HCI and explores various strategies for designing inclusive interfaces. The paper also discusses the challenges and opportunities in implementing inclusive design practices and provides recommendations for future research and development in this field.